Conflict in Independent Catholic Schools - Guernsey, Dan; Barott, James (Catholic Education: A Journal of Inquiry and Practice, 2008)
Independent Catholic schools are a growing phenomenon in the Catholic Church in America. This article provides a contextualized account of the phenomenon by examining via a field observation the experience of two independent Catholic schools in two different dioceses. These schools were founded in conflict and beset by continued conflict to the point of splitting; first from the diocese, then again with themselves. An environment of religious conflict motivated laity to open their own schools to socialize their children into a traditional notion of the Catholic faith. In both independent schools examined, conflict about governance, between founding parents and new stakeholders who joined the schools, led to each of the schools splitting; thus, the two became four. Each of the new breakaway schools was structured and governed much like the original schools, albeit with some increased openness to parental input. Second generation breakaway splits further complicated the relationship between these schools and their dioceses. While the limited sample prohibits highly generalizable data, the account suggests some preliminary conclusions about trends witnessed in the experience of these schools and suggests lines for further inquiry in this relatively unexamined phenomenon.